Recalcitrant Ulcerative Pyoderma Gangrenosum of the Leg Responsive to Tildrakizumab: A Case Report - Leow LJ; Zubrzycki N (Dove Medical Press, 2022)
Liang Joo Leow,1- 3 Nicolas Zubrzycki1 1Aesthetic Dermatology, Sydney, NSW, Australia; 2Department of Dermatology, St Vincent's Private Hospital, Sydney, NSW, Australia; 3St Vincent's & Mater Clinical School, University of Notre Dame Australia, Sydney, NSW, AustraliaCorrespondence: Liang Joo Leow, Aesthetic Dermatology, 69 Burton Street, Darlinghurst, NSW, 2010, Australia, Tel +61 2 9188 2080, Email drleow@aestheticdermatology.com.auAbstract: Elevated levels of inflammatory mediators-including the interleukin IL-23-are implicated in the pathogenesis of pyoderma gangrenosum (PG), an autoinflammatory neutrophilic dermatosis characterized by rapidly enlarging, suppurative ulcers and cribriform scarring. Here, we present the first case report of significant response of isolated ulcerative PG with tildrakizumab, a biologic agent directed against the p19 subunit of IL-23, in an elderly woman with extensive treatment-refractory PG on her left leg. Tildrakizumab (100 mg subcutaneously at weeks 0 and 4, then every 8 weeks, and eventually increased in frequency to every 6 weeks), combined with acetic acid soaks each morning and chemical debridement every evening with 3% hydrogen peroxide, resulted in progressive decrease in ulcer size and depth, re-epithelialization, and recovery of sensory perception. This report describes the dramatic clinical response of ulcerative PG on the leg with tildrakizumab.Keywords: interleukin-23, leg ulcers, pyoderma gangrenosum, biological drug, wound dressing